Predicting homework motivation and homework effort in six school subjects: The role of person and family characteristics, classroom factors, and school track - Trautwein, Ulrich; Lüdtke, Oliver (Learning and instruction, 2009)
This study examines the determinants of homework motivation and homework effort in six school subjects at three levels: student level, classroom level, and school level. We hypothesized that several factors—including stable personality characteristics such as gender and conscientiousness, students' domain-specific homework motivation, and characteristics of homework assignments—have concomitant effects on student homework effort. The sample consisted of 511 students in Grades 8 and 9. Across all six school subjects, multilevel modelling showed that students' homework motivation and homework effort varied primarily as a function of their shared perceptions of homework quality and control (classroom level) and of their conscientiousness, individual perception of homework quality, and expectancy and value beliefs (student level). Domain-specific patterns were found for student gender in line with gender stereotypes. Cognitive ability, family background, and parental homework help or control were only loosely associated with homework motivation and homework effort.